Preparation and Characterization of Magnetic Chitosan/Cu-Mg-Al Layered Double Hydroxide Nanocomposite for the One-Pot Three-Component (A(3)) Coupling of Aldehydes, Amines and Alkynes - Nikkhoo, Mohammad; Amini, Mojtaba; Farnia, S. Morteza F.; Mandavinia, Gholam Reza; Gautam, Sanjeev; Chae, Keun Hwa (SPRINGER, 2018)
Magnetic chitosan/Cu-Mg-Al layered double hydroxide (mCSLDH) nanocomposite was prepared and copper(II) ions were immobilized in the prepared composite. The nanocomposite [(Cu-mCSLDH)] was characterized by FT-IR, XRD, VSM, AAS, EDX, SEM and TEM. The utility of nanocomposite was investigated in the one-pot three-component (A(3)) coupling of aldehydes, amines and alkynes to produce propargylamines. The Cu-mCSLDH nanocomposite is found to be highly efficient and recyclable heterogeneous catalyst.
Keywords: EFFICIENT; COMPOSITES; COMPLEXES; CATALYSTS; LDH